A articulação da leitura e da escrita de textos acadêmicos para elaboração do TCC : análise de uma turma de pós Proeja na EAD - Lacerda, Luciane Ferreira (2017)
In this work the researcher investigated teachers practice concerning the reading and writing of students from Post Proeja in online classes, aiming at analyzing the process of reading and writing academic texts for the course ending task (Trabalho de Conclusão de Curso / TCC)). As theoretical foundation, the concepts of literacy and academic literacy by Fiad (2013), Street (2010), Rojo (2004), Soares (2004) e Leffa (2001) among others were used. To gather the data for this research, a case study was chosen as part of the methodology when observations on interaction during online classes could be done in order to verify how the academic text is taught and required by the instructors. Besides those observations, there were also interviews with students and the course staff, subjects of this research. Considering the difficulty in writing the TCC, although many students in this research come from undergraduation courses where they had contact with this literacy gender, their TCC written performance is still inefficient. As a conclusion, it was evident that the academic writing constitutes a kind of literacy that shall be developed at college, because, for most of the students, this is a new gender and it only happens when the students enter college. So, teachers must instruct their students starting from the basic steps in the academic writing process, emphasizing their needs on reading, writing and rewriting the academic texts.